ANALISIS RAGAM PROBLEMATIKA KETERAMPILAN MEMBACA PESERTA DIDIK KELAS RENDAH DI SEKOLAH DASAR: Penelitian Studi Kasus Kualitatif - Diah Wardani, Anisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze various problems experienced by students in reading beginning in grade I of elementary school. The type of research used is qualitative research with a case study research method with data collection techniques in the form of observation, tests, and documentation. The subject of this study is class I students consisting of 24 students in one of the elementary schools in Musi Rawas. Based on the results of the study, there are various problems experienced by grade I students, namely students who have not memorized letters, difficulty distinguishing letters and eliminating letters, slow spelling skills, lack of interest and low motivation, and less than optimal teacher ability. So based on these problems, researchers offer various solutions in the form of interesting and varied media and methods to attract the attention of students.